Derivative Spectrophotometric Method for Simultaneous Determination of Nickel(II) and Copper(II) Using 6-(Anthracen-2-yl)-2,3-dihydro-1,2,4-triazine-3-thione - Barazeh Tehrani, M.; Mirkamali, S.M.S.; Souri, E.; Foroumadi, A. (Asian Journal of Chemistry, 2012)
Derivative spectrophotometric method using newly synthesized reagent, 6-(anthracen-2-yl)-2,3-dihydro-1,2,4-triazine-3-thione (ADTT), has been developed for the simultaneous determination of copper and nickel. The reagent was synthesized by the acylation of anthracene and then reaction of the resulted product with amylnitrite to produce (anthracen-2-yl)-glyoxal aldoxime. After addition of thiosemicabazone the reagent was prepared. Copper and nickel were determined by using zero-crossing method in the second, third and fourth order derivative spectra after derivatization in basic medium. Beers's law was obeyed in the range of 5-35 μg/mL for copper at 387 nm (second order) and 554 nm (third order) and 5-35 μg/mL nickel at 447 nm (first order), 400 nm (third order) and 385 nm (fourth order). The limit of quantification was 5 μg/mL for both cations. The within-day and between-day variations in three concentrations were less than 3.36 and 4.73 % in all measurements, respectively. The proposed method is simple and accurate for determination of binary mixtures.